Influence of the State of the Mating Friction Elements of the Drum Brake on the Outer Thermal Field - T. Orzechowski (Engineering Transactions, 2015)
The analysis presented below concerns the thermal field of the outer surface of the drum brake registered by means of an AGEMA Series®900LW thermovision camera and the LINY software. Roundness deviations of the inner surface of the drum measured with a TALYROND precise measurement device were compared with the distribution of temperature on the outer surface along the circumference. The results show that these quantities are interdependent and the coefficients of correlation calculated for them are always greater than 0.8. What is more, they are not affected by the type of pressure (i.e. shoe). The distribution of temperature along the generating line of the drum represents the character of the contact between the shoe and the drum. Tests carried out for yarious arrangements of friction members of the drum brake confirmed the interdependence of the thermal field and the geometry of mating surfaces. A maximum temperature rise of the drum has also been discussed.